Analisis Kebijakan Pengelolaan Website Perpustakaan IAIN Curup dan Kaitannya Dengan Peningkatan Pelayanan Perpustakaan - Budiman, Budiman (El-Idare: Journal of Islamic Education Management, 2021)
Policy Analysis of IAIN Curup Library Website Management and Its Relation to Improving Library Services". One of the agencies that use the website as a medium of information is the IAIN Curup Library. The formulation of the problem in this study is how the policy of managing the IAIN Curup library website and its relation to improving library services is This type of research is carried out with a field study approach (field research). The data that has been collected is analyzed by means of descriptive-analysis The results of the study indicate that the policy of managing the IAIN Curup Library website is related to the obligation for librarians to provide information regularly to library membersThe function and purpose of the IAIN Curup Library website is to publish information, make it easier for students to obtain information on books, submit thesis requirements, or find out about events held by the library.